25 Involvement in palliative and end of life care research. (13th October 2019) - Mathie, Elspeth; Jones, Julia; Jacobs, Lorna; Rhodes, Graham; Harvey, Catherine; Thakrar, Sanjay
Abstract : Involvement of those with experience of using care services is now an important and mandatory part of health and social care research, including palliative and end of life care. Those with direct experience of using palliative and end of life care (patients, carers, friends or family members), such as hospices and care homes can enhance and shape research (Goodman et al., 2011). The distinction is made between 'participants' in studies who provide 'data' and research carried out 'with' or 'by' members of the public (as defined by INVOLVE). Involvement in these research areas, has its own challenges (Backhouse et al., 2016; Mockford et al., 2016) and innovative approaches are needed (Brighton et al., 2018). Seeking involvement from people with experience of care at an early stage of research development is key to ensure the research is user-friendly, feasible and has relevant outcomes. Three organisations ran a joint workshop focussing on palliative and end of life care to enable researchers to receive face to face comments from people with experience of palliative and end of life care on their research projects in a 'dragon's den' style session. We will share 1) our experience of this approach to involvement, 2) the experiences of the people who took part and 3) findings from the post evaluation. We will also outline the challenges of involving people in this research area, the importance of 'feedback' to those taking part (Mathie et al, 2018) and our learning for the future.